2008
DOI: 10.1002/qua.21781
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of electron density as a result of hydrogen bond formation

Abstract: It has been found that the amount of charge transfer between donor and acceptor molecules in four sets of hydrogen-bonded complexes may be adequately described as an exponential function of the equilibrium distance between the hydrogen atom and the nearest atom of the acceptor molecule. The exponential factors of the transfer are of the same order but somewhat larger than the factors found otherwise in the investigations of dynamic electron transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It was previously shown that charges of the substituent active region, qSAR(X), correlated fairly well with the Hammett constants in monosubstituted benzenes [62], carboxylic acids [58,63], and substituted tetrazoles [64]. On the other hand, the constants correlated well with the properties of reaction sites, e.g., with the charges and potentials at H atoms of COOH group [58].…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…It was previously shown that charges of the substituent active region, qSAR(X), correlated fairly well with the Hammett constants in monosubstituted benzenes [62], carboxylic acids [58,63], and substituted tetrazoles [64]. On the other hand, the constants correlated well with the properties of reaction sites, e.g., with the charges and potentials at H atoms of COOH group [58].…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, the constants correlated well with the properties of reaction sites, e.g., with the charges and potentials at H atoms of COOH group [58].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations